Project Estimating and Cost Management - Rad, Parivs (Berrett-Koehler Publishers, 2001)
Improve the accuracy of project estimates and make better in-progress modifications by following the discipline-independent approach mapped out in this book. Learn the best ways to apply new tools, including a breakdown structure for both work and resources and proven estimating models. In addition, you'll gain insights into best practices for progress monitoring and cost management, as well as for dealing effectively with external projects.